HMGB1 and inflammatory cytokines in experimental acute lung injury induced in rabbits - Kurokawa, C. S. [UNESP] (2020)
The aim of this work was to measure HMGB1, TNF-alpha, and IL-8 in bronchoalveolar lavage (BAL), serum and TLR2 and TLR4mRNA expression in lung tissue of rabbits with two grades of acute lung injury (ALI). The animals were randomly assigned to groups with severe (S) and mild/moderate (MM) ALI, induced with warm saline, and a control group. HMGB1, TNF-alpha, IL-8, TLR2mRNA and TLR4mRNA were measured after ALI induction. The results showed increased levels of IL-8, TNF-alpha, HMGB1 and TLR4mRNA in the ALI groups. HMGB1, IL-8 and TNF-alpha concentrations in BAL were higher in S compared MM. Increased TLR4mRNA was observed in S and MM versus control. The results suggest an early participation of HMGB1 in ALI together with IL-8 and TNF-alpha and association with severity. TLR4 has early expression and role in ALI pathophysiology but is not associated with severity.